Enhancing value chains an agenda for APEC : a report of the CSIS Simon Chair in Political Economy and Scholl Chair in International Business, November 2013 - Goodman, Matthew; Miller, Scott (CSIS report, 2015)
Economic integration has been a focus of Asia-Pacific affairs for the last quarter century. To support and strengthen economic ties, governments in the region have pursued an array of integration initiatives, from the Asia-Pacific Economic Cooperation (APEC) forum launched in 1989 to bilateral and regional trade negotiations currently underway